Bismuth coordination networks containing deferiprone: synthesis, characterisation, stability and antibacterial activity1. Issue 31 (21st August 2015) - Burrows, Andrew D.; Jurcic, Monika; Mahon, Mary F.; Pierrat, Sandrine; Roffe, Gavin W.; Windle, Henry J.; Spencer, John
<x xml:space="preserve">Abstract</x> Bismuth–dicarboxylate–deferiprone coordination networks release the iron overload drug deferiprone on treatment with PBS and demonstrate antibacterial activity against H. pylori.